Mechanisms of Neoantigen-Targeted Induction of Pyroptosis and Ferroptosis: From Basic Research to Clinical Applications - Yu, Jie; Wang, Qing; Zhang, Xiaoyun; Guo, Zhiliang; Cui, Xiaodong (Frontiers in Oncology, 2021)
Neoantigens are tumor-specific antigens (TSAs) that are only expressed in tumor cells. They are ideal targets enabling T cells to recognize tumor cells and stimulate a potent antitumor immune response. Pyroptosis and ferroptosis are newly discovered types of programmed cell death (PCD) that are different from apoptosis, cell necrosis, and autophagy. Studies of ferroptosis and pyroptosis of cancer cells are increasing, and strategies to modify the tumor microenvironment (TME) through ferroptosis to inhibit the occurrence and development of cancer, improve prognosis, and increase the survival rate are popular research topics. In addition, adoptive T cell therapy (ACT), including chimeric antigen receptor T cell (CAR-T) technology and T cell receptor engineered T cell (TCR-T) technology, and checkpoint blocking tumor immunotherapies (such as anti-PD- 1 and anti-PD-L1 agents), tumor vaccines and other therapeutic technologies that rely on tumor neoantigens are rapidly being developed. In this article, the relationship between neoantigens and pyroptosis and ferroptosis as well as the clinical role of neoantigens is reviewed.